Aspenia online: international analysis and commentary (Aspen Institute Italia, 2022)
"Aspenia online is characterized by original, short, to-the-point articles – allowing us to continue the cultural and policy debates opened by the print version of Aspenia. We view these two outlets as complementary, sharing an interdisciplinary approach to international issues and a specific focus on the evolution of the US and Europe in the global context."